Fe, Zn AND S CONTENT IN DOUBLED HAPLOID LINES OF CHINESE SPRING × SQ1 WHEAT POPULATION - A. I. Abugalieva; S. I. Abugalieva; S. A. Quarri; E. K. Turuspekov; I. Chakmak; T. V. Savin; V. A. Ganeev (Вавиловский журнал генетики и селекции)
A mapping population of 95 doubled haploid lines of wheat Triticum aestivum L., raised by crosses between cultivar Chinese Spring (CS) and line SQ1, was grown in irrigated and rainfed conditions of South-East Kazakhstan (1998–2008 years), studied for grain quality traits, and characterized for Fe, Zn, and S content in grains. In addition to previous studies associated with grain productivity and drought stress torelance (Quarrie et al., 2005) and grain quality traits (Abugalieva et al., 2008), the range of variation in micronutrient contents in wheat grains of the CS × SQ1 doubled haploid population provides an excellent opportunity for identification of quantitative trait loci that control the amounts of Fe, Zn, and S in grains. Doubled haploid lines with stable high content of Fe and Zn grown in irrigated and rainfed conditions were obtained on the base of the referred work. The lines can be used in biofortification of spring wheat in Kazakhstan. The results reveal significant correlation indices between Zn and protein contents in grains. They may be important in local breeding programs for the improvement of productivity and grain quality.